Ethical Hacking: The Story of a White Hat Hacker (International Journal of Innovative Research in Computer Science & Technology, 2020)
Massive growth of the Internet has brought  in many good things such as e-commerce, easy access to  extensive sources of learning material, collaborative  computing, e-mail, and new avenues for enlightenment and  information distribution to name a few. Today, since almost  all the work is done over the internet, crucial data is sent  over the web and other information is placed over the  internet. So ensuring data security over the internet is very  important and should be taken care of at utmost priority. As  with most technological advances, there is also a dark side  attached to it, i.e. hacking. Hacking is an activity in which a  person (namely hackers) exploits the weaknesses and  vulnerabilities in a system for self profit or gratification.  With the growing movement of the world from offline to  online culture like shopping, banking, sharing information  access to sensitive information through the web applications  has increased. Thus the need of protecting the systems from  hacking arises to promote the persons who will punch back  the illegal attacks on the computer systems and will ensure  data security. As every coin has two faces, this coin also has  one another face which generally acts as a life saver for the  victims of hacking. This lifeguard technique is called ethical  hacking.  Ethical hacking is a technique which is used to identify the  weaknesses and vulnerabilities in the system or computer  network in order to strengthen the system further to prevent  the data. The main reason behind studying ethical hacking  is to evaluate target system security. This paper helps to  generate a brief idea of ethical hacking and all aspects.
Keywords: Hacking; Hacker, Hacking; Ethical Hacking; Red Hat Hacker